Reproductive technology and surrogacy : a global perspective - Ásgeirsson, Hrafn; Nordal, Salvör (TemaNord., 2015)
During the past few years, reproductive technology and surrogacy have emerged in a number of European countries as issues of debate. There has been a steady increase in the use of reproductive technology in the Nordic countries, as well as an increase in the use of cross-border medical treatment in order to achieve pregnancy. At the same time, a number of ethical issues have been raised concerning the rights of the participants, including the children. In the fall of 2013, the Nordic Committee on Bioethics organised a conference in Reykjavik that focused on the current situation in the Nordic countries and on the global aspects of reproductive technology and surrogacy, including the market that is emerging in this field. This conference summary highlights the main ethical issues facing researchers, policymakers and practitioners who deal with these issues.